EFFECTS OF WATER STRESS AND RECOVERY PERIODS ON TOTAL LIPID AND FATTY ACIDS IN CUCUMIS MELO VAR. FLEXUOSUS (L.) NAUDIN AND RELATED SPECIES - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2019)
Water stress (drought) is one of the most important abiotic factors influencing plant growth parameters, accompanied by changes in biomass ratios and physiological and biochemical alterations depending on the severity and duration of drought exposure, as well as plant species. Total lipids and fatty acids (FA) are major components of the plant cell, and can be used to understand changes in cell lipid concentrations under water stress. In this study, the aim was to investigate the responses of total and fatty acids (FA) being major components of the plant cell, are required to be understood of changes of compositions of cell lipids under two water stress levels and recovery periods by rewatering of Cucurbitaceae members. Total lipid and gas liquid chromatography (GLC) analyses indicated that the species behaved differently with respect to water stress levels and recovery periods. Linolenic (18:3) and eiocosenoic acid (20:1) accounted for the biggest proportion of FA in all species. The major effect of water stress was seen in proportions of 18:3, which increased significantly in leaves of Cucurbita pepo under moderate stress (MS) and severe stress (SS), whereas it remained unchanged in Cucumis melo under both treatments, but decreased significantly under SS in Ecballium elaterium. During recovery, further changes in FA percentages occurred at different rates in individual species. For the short recovery period determined after 2 days rewatering, the total leaf lipid content increased significantly in previously stressed plants. The effect of the longer recovery period (4d rewatering), was accompanied by a continued increase of total lipid content in all plants in previous MS and SS treatments, and was significant in MS and SS Ecballium compared to control plants.
Keywords: Water stress; Cucurbitaceae; Cucumis; Lipids; Fatty acids; Recovery; MEMBRANE-ENRICHED FRACTION; DROUGHT-STRESS; PHOSPHOLIPID-COMPOSITION; SOLUBLE SUGARS; METABOLISM; TOLERANCE; SEEDLINGS; LEAVES; DEHYDRATION; DEFICITS